PENGARUH MOTIVASI KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA GURU SMK PGRI PEKANBARU - Delvi Yuliani Delvi Yuliani; Sumarno Sumarno '; Sri Kartikowati Sri Kartikowati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aims to find out the influence of Work Motivation and Organizational Climate on Performance of Teachers. Population in this study is all teachers of SMK PGRI Pekanbaru which is determined as sample of the study taken by census sampling technique. Data is collected using questionnaires and documentation. Data is analyzed using multiple linear regression analysis, t test and f test with significance level of 0.05%. The research shows that the Work Motivation and Organizational Climate simultaneously is positive and has significant impact on teacher performance. This is based on the results of the analysis, which shows the calculation results F test> F table (52.298> 3.25). Furthermore, with the T test to determine whether each of the independent variables (Work Motivation and Organizational Climate) have an effect on the dependent variable (Teacher Performance). The results shows a partial Work Motivation is positive and has significant influence on teacher performance. This is evidenced where t test> t table (2.517> 1.687). Next to the Organizational Climate variables show that also has a positive and significant influence on Teacher Performance. This is evidenced where t test> t table (7.812> 1.687). The predictive ability of the variables on Teacher Performance in this study only amounted to 73.9% (R Square 0.739) while the remaining 26.1% is influenced by other factors that are not researched in this research.Keywords : work motivation, organizational climate, performance of teachers